Clinical significance of estrogen receptor gene ERS1 SNP in cancer patients from families with oncological pathology in pedigrees - Paliychuk, O.V; Polishchuk, L.Z.; Rossokha, Z.I.; Chekhun, V.F. (Онкологія, 2016)
Aim: to determine genetic risk of oncologic pathology development in family trees of
probands from families with family cancer history and patients with primary-multiple
tumors basing on the results of clinical-genealogical examination and genetic analysis of estrogen receptor gene ESR1 in patients with ovarian cancer and breast cancer. Methods: clinical, morphological, clinical-genealogical and molecular-genetic
studies. Results: it was presented the results of complex of 145 females: 90 patients
with cancer of female reproductive system organs (FRSO), including patients with
primary-multiple tumors with aggregation of tumor pathology in families, and 55 females — control group without cancer family history. It was determined that in families of patients with FRSO cancers the malignant tumors of FRSO, gastro-intestinal
tract and others prevail that corresponds to Lynch II syndrome (family cancer syndrome). Molecular-genetic examination of single nucleotide polymorphism (SNP)
of the gene ESR1 in genomic DNA of peripheral blood and from histological material determined significant increase the frequency of 397СС genotype of the gene
ESR1 in cancer patients and aggregation of malignant pathology in families comparing with frequency of this genotype in female of control group. Statistical processing of these results demonstrated that the risk of malignant pathology development
(odds ratio — OR, 95% confidence interval — СІ) increases in 4.95 times in case of
determination of СС genotype of the gene ESR1 (T-397C), and in case of heterozygous carriage of this gene — in 2.25 times. The presence of TT genotype of the gene
ESR1 (T-397C) reduces the risk of the disease (OR = 0.21). Conclusion: the frequency of АА, AG, GG genotypes of the gene ESR1 (A-351G) also differed in cancer patients comparing with these characteristics in healthy females: significant reduction AA genotype АА to 33.33% versus 67.27% in healthy females (p = 0.001),
significant increase of AG genotype from 32.73 to 57.78% (p = 0.006), tendency of
genotype GG increase — from zero to 8.89% (p = 0.057). This is a basis for clinical-genealogical and molecular genetic study in females with FRSO malignant pathology for detection of polymorphisms (SNP) of estrogen receptor gene (ESR1). The
examined SNPs polymorphisms of ESR1 can be predictors of cancer development
and aggregation of malignant tumors in proband’s family and progeny. Стаття присвячена визначенню генетичного ризику виникнення онкологічної патології у родинах пробандів із сімейною історією раку (пробанди — хворі на рак молочної залози, рак яєчника,
первинно-множинні пухлини) шляхом оцінки результатів клініко-генеалогічного обстеження хворих
та генетичного аналізу мутацій (SNP — однонуклеотидний поліморфізм) гена рецептора естрогена ERS1. Методи дослідження: клінічний, морфологічний, клініко-генеалогічний, молекулярно-генетичний, статистичний. Результати: серед обстежених
було 90 хворих на рак і 55 здорових жінок без випадків раку у родоводах (група контролю). Встановлено, що асоціація злоякісних пухлин у родоводах хворих жінок відповідала сімейному раковому синдрому
(синдром Лінча II типу). Примолекулярно-генетичному дослідженні геномної ДНК периферичної крові
та гістологічного матеріалу пухлин визначено достовірне підвищення частоти генотипу 397СС гена
ESR1 у хворих на рак з агрегацією злоякісної патології у родинах порівняно з частотою цього генотипу у жінок із групи контролю. Статистичний аналіз показав, що ризик розвитку злоякісної патології
(відношення шансів — ВШ; 95% довірчий інтервал —
ДІ) підвищується у 4,95 раза у випадках СС генотипу гена ESR1 (T-397C), а у разі гетероносійства
цього гена — у 2,25 раза. За наявності ТТ генотипу
гена ESR1 (T-397C) ризик розвитку раку знижується (ВШ 0,21). Висновок: частота генотипів АА, AG,
GG гена ESR1 (A-351G) також відрізняється у хворих на рак порівняно зі здоровими жінками: значне
зниження частоти АА генотипу до 33,33% порівняно з 67,27% у здорових жінок (p = 0,001), значне
підвищення частоти AG генотипу із 32,73 до 57,78%
(p = 0,006), тенденція до зростання частоти GG генотипу — від 0 до 8,89% (p = 0,057). Одержані результати є основою для проведення клініко-генеалогічних та молекулярно-генетичних досліджень
у родинах з агрегацією раку органів жіночої репродуктивної системи для детекції SNP гена ESR1. Виявлений SNP поліморфізм вказаного гена може бути
предиктором розвитку раку та агрегації злоякісних
пухлин у родинах пробандів та їх нащадків.